2009
DOI: 10.1109/tuffc.2009.1329
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional photoacoustic imaging using a two-dimensional CMUT array

Abstract: In this paper, we describe using a 2-D array of capacitive micromachined ultrasonic transducers (CMUTs) to perform 3-D photoacoustic and acoustic imaging. A tunable optical parametric oscillator laser system that generates nanosecond laser pulses was used to induce the photoacoustic signals. To demonstrate the feasibility of the system, 2 different phantoms were imaged. The first phantom consisted of alternating black and transparent fishing lines of 180 mum and 150 mum diameter, respectively. The second phant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(58 citation statements)
references
References 28 publications
2
55
0
1
Order By: Relevance
“…Compared to previous PA imaging systems employing 2-D array US transducers, [12][13][14] this system provides sub-millimeter spatial resolution, enables fast PA data acquisition, and incorporates real-time 3-D US imaging functionality of the commercial US scanner system. The current DAQ system acquires the PA data set for one volumetric frame in ∼20 sec from 36 laser firings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to previous PA imaging systems employing 2-D array US transducers, [12][13][14] this system provides sub-millimeter spatial resolution, enables fast PA data acquisition, and incorporates real-time 3-D US imaging functionality of the commercial US scanner system. The current DAQ system acquires the PA data set for one volumetric frame in ∼20 sec from 36 laser firings.…”
Section: Discussionmentioning
confidence: 99%
“…Khuri-Yakub et al have fabricated a 2-D capacitive micromachined ultrasonic transducer (CMUT) with 16 × 16 elements (pitch size, 250 μm) for PA and US imaging. 12 Mechanical scanning was needed to form a large detection aperture to improve the image quality. Zhu et al have developed a 2-D array US transducer with 10 × 128 elements for US and PA characterization of ovarian tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to traditional piezoelectric technology, CMUTs are known for having a fractional frequency bandwidth usually wider than 100%. 26 Therefore, CMUT technology is particularly attractive for wideband imaging applications such as photoacoustic imaging 27 or contrast agent imaging, 28 or as a hydrophone. 29 In a previous study, Novell et al demonstrated that a CMUT array could be exploited to enhance the signal from contrast agents by recording the microbubble response at subharmonic and second harmonic frequencies simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…2 Another method employs a 2D capacitive micromachined ultrasonic transducer (CMUT) to collect the volume data. 3 The other includes collocation of piezoelectric transducers. P. Ephrat et al arranged fifteen commercial transducers to constitute a sparse array.…”
Section: Introductionmentioning
confidence: 99%